STUDI PEMISAHAN PATI DAN MALTOSA MENGGUNAKAN MEMBRAN KOMPOSIT PMMA - BENTONIT - POLIAMIDA - Rusli, Handajaya
Starch and maltose are constructed chemically by glucose. Maltose can be produced by starch hydrolisis. The objective of this research is to obtain a prospective membrane material serving as membrane bioreactor. Separation of starch and maltose is a way to increase the efficiency of enzymatic hidrolysis of starch to maltose. A great difference of size between starch and maltose can be considered as a basis view of separation using microporous membranes as filter. In this research, such a membrane was made by blending PMMA and bentonite, with a ratio of 3:1, as supporting layer. The obtained membrane could separate starch solution in feed with a percent rejection varying between 40 – 70%, while < 5% for maltose. Composite membrane was prepared by interfacial polymerization of TMC and MPD on PMMA – bentonite membrane as supporting layer. The performance of such a membrane couldn’t be measured in this experiment. The obtained composite membrane seemed to be very dense. Thus, there was no permeation of water, nor starch and maltose, towards the membrane observed, for the operasional pressure applied (until 3 bar).